Research on the Efficient Recovery Technology of Gold Mineral in an Oxidized Ore - Ji Qiang; Li Guangsheng; Zhu Xingfu; Gao Tengyue; Cai Mingming (E3S Web of Conferences)
In view of the characteristics of high content of gold minerals in limonite and great difficulty of flotation recovery, the research on process mineralogy and efficient recovery technology was carried out respectively. The results of process mineralical analysis show that the particle size of gold mineral particles is coarse, the average particle size is 18.33μm, and the associated content with limonite is 28.36%, which is difficult to recover by a single flotation process. Through the efficient recovery technology research, the combined process of heavy dressing and flotation can realize the efficient recovery of gold mineral, and can obtain the mixed gold concentrate grade of 41.96g/t, the recovery rate of 88.21%, the grade of tailings gold reduced to 0.57g/t, difficult for the efficient recovery of gold resources, and provide technical support by increasing the economic benefit of enterprises.